Reflecting on How Social Impacts are Considered in Transport Infrastructure Project Planning: Looking beyond the Claimed Success of Sydney's South West Rail Link. Issue 3 (2nd July 2020) - Mottee, Lara K.; Arts, Jos; Vanclay, Frank; Miller, Fiona; Howitt, Richard
ABSTRACT: Urban rail transport megaprojects are promoted as generating positive social change at a metropolitan scale, yet they produce complex unplanned negative impacts at local scales. Environmental and Social Impact Assessment (ESIA) and its follow-up help decision-makers assess and manage the social and environmental impacts of major projects. Using Western Sydney's politically-successful South West Rail Link as an example, we identified the practice challenges and governance barriers to applying ESIA and EIA follow-up across spatial scales. These challenges and barriers influence the planning and management of the impacts of integrated urban development and transport infrastructure development.